2014
DOI: 10.1136/amiajnl-2014-002841
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social networking sites on health behavior change: a systematic review and meta-analysis

Abstract: Our study showed a positive effect of SNS interventions on health behavior-related outcomes, but there was considerable heterogeneity. Protocol registration The protocol for this systematic review is registered at http://www.crd.york.ac.uk/PROSPERO with the number CRD42013004140.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
432
3
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(483 citation statements)
references
References 66 publications
20
432
3
8
Order By: Relevance
“…However, much uncertainty exists in terms of ethics and safety [10]. Furthermore, social media seemed to be an efective method to promote health-related behaviours [11].…”
Section: Online Social Networking Beneits Of Online Social Netwmentioning
confidence: 99%
“…However, much uncertainty exists in terms of ethics and safety [10]. Furthermore, social media seemed to be an efective method to promote health-related behaviours [11].…”
Section: Online Social Networking Beneits Of Online Social Netwmentioning
confidence: 99%
“…Advantages of this type of intervention are related to the fact that social networks have the potential to reach hundreds, thousands and even millions of users (25) , especially those from younger age groups (31) . Another way to use social networks would be to perform nursing interventions through text messages, which may be especially advantageous for promoting physical activity or eating behaviors, for example (41,44,59) . Interventions of this kind have advantages compared to traditional face-to-face interventions, being that the participant does not need to attend the sessions in person and has unlimited access to the intervention materials whenever they wish (41) .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence we do have is often either descriptive or based on small-scale trials [4,[12][13][14][15] creating the risk that social marketers will incorporate Facebook into their campaigns without considering the role the platform would play. [16] Of note, though, is a Western Australian analysis of the Make Smoking History and LiveLighter campaign pages, which found that testimonials and informative posts generally achieved higher engagement and reach than other types of communication techniques.…”
Section: Introductionmentioning
confidence: 99%